ALIH AKSARA DAN ALIH BAHASA TEKS KISAH NABI MUSA AS DALAM NASKAH TEKS CERITA NABI-NABI VERSI AZHARI AL-KHALIDI RAHMATULLAH - Elsis, Ella; Hasanuddin WS, Hasanuddin WS; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2013)
This article was written to (1) describe of teks story about Musa prophet at text Strory of Prophets version Azhari Al-khalidi Rahmatullah, (2) describe the translation of story about Musa prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah, (3) describe change language of story about Musa prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah. The objeck of this study were story about Musa prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah. The text was data processing by four step, is roundup of data, describe of the text, translation, and change language. The finding of the study is avalaible of text about Musa prophet at text Story of Prophets version Azhari Alkhalidi Rahmatullah in Latin script and Indonesian language and more words that indicate old language charactheristic.